Inevitable Loss and Prolonged Grief in Police Work: An Unexplored Topic - Papazoglou, Konstantinos; Blumberg, Daniel M.; Collins, Peter I.; Schlosser, Michael D.; Bonanno, George A. (Frontiers in Psychology, 2020)
The present manuscript presents foundational constructs related to death and loss (i.e., grief, bereavement, prolonged grief) providing empirical findings from recent research on the impact of death and loss on police officers’ health, behavior, and overall functioning. Police officers are routinely exposed to death. In many instances, officers’ contact with decedents includes, among others, victims of accidents, catastrophes, or violent crimes and witnessing the intense emotional suffering of relatives of the deceased. Additionally, it is not uncommon for officers to experience the loss of fellow officers from on-duty deaths and permanent, career-ending injuries. Simultaneously, like everyone, police officers have to cope with deaths of loved ones in their personal lives. The result is that officers’ health and well-being are likely compromised because of the systematic exposure to on- and off-duty deaths. In this perspective paper, death and loss in law enforcement are explored in an attempt to raise awareness and increase attention to this area of police work. In addition, the authors list a number of prophylactic intervention strategies that would support officers cope with the impact of loss and death and promote their own resilience.